Satellite Ozone and UV Measurements over Cyprus - Charalampous, G.; Fragkos, Konstantinos; Nisantzi, Argyro; Fountoulakis, I.; Papachristopoulou, Kyriakoula; Hadjimitsis, Diofantos G.; Kazadzis, S. (My University, 2023)
Ultraviolet (UV) radiation is a small but significant part of solar radiation that reaches the Earth's surface. Overexposure to UV radiation can have harmful effects on human health and ecosystems, including sunburn, skin cancer, eye damage, and immune system weakening. The factors that affect UV levels at the surface include solar elevation angle, total ozone amount, optical properties of aerosols, clouds, altitude, and surface albedo. Ozone is an efficient absorber of UV radiation, and its depletion leads to increased ground-level UV radiation. The recovery of the ozone layer in response to the phaseout of ozone-depleting substances is also linked to climate change, which can also affect future UV levels. Therefore, it is crucial to continuously monitor UV radiation levels. The Ultraviolet Index (UVI) is a tool that increases public awareness of the need for sun protection and lowers the risk of skin cancer. Cyprus, as the European country with the highest sunshine duration, is an ideal location for studying UVI levels and ozone column amounts. In this study, we present a climatology of ozone and UVI over the four major cities in Cyprus (Nicosia, Limassol, Larnaca, and Paphos) based on satellite overpass measurements from the Ozone Monitoring Instrument for the period 2004-2022. We also investigate the sensitivity of UV radiation to ozone changes using the radiation amplification factor and also to aerosol and clouds. This study provides valuable insights into the climatology of ozone and UVI in Cyprus and the sensitivity of UV radiation to ozone changes, which can aid in the development of effective public health policies and sun protection measures.
Keywords: OMI; ozone depletion; radiation amplification factor; UV index